Physiological Indices of Elite Junior - I Alpine Skiers. - Axtell, Robert (1996)
Keywords: dept.hms; faculty_collection; sabbatical_report

Growing Artificial Societies Social Science from the Bottom Up - Epstein, Joshua M.; Axtell, Robert (Complex adaptive systems, 1996)
How do social structures and group behaviors arise from the interaction of individuals? Growing Artificial Societies approaches this question with cutting-edge computer simulation techniques. Fundamental collective behaviors such as group formation, cultural transmission, combat, and trade are seen to "emerge" from the interaction of individual agents following a few simple rules. In their program, named Sugarscape, Epstein and Axtell begin the development of a "bottom up" social science that is capturing the attention of researchers and commentators alike. The study is part of the 2050 Project, a joint venture of the Santa Fe Institute, the World Resources Institute, and the Brookings Institution. The project is an international effort to identify conditions for a sustainable global system in the next century and to design policies to help achieve such a system. Growing Artificial Societies is also available on CD-ROM, which includes about 50 animations that develop the scenarios described in the text. Copublished with the Brookings Institution.
Keywords: Social sciences; dept.hms; faculty_collection

Academic preparation of athletic trainers as counselors - Misasi, S.P.; Davis Jr., C.F.; Morin, G.E.; Stockman, D. (Journal of Athletic Training, 1996)
Athletic trainers have assumed several roles and responsibilities over the years, but perhaps there is no more important role than that of a counselor. Are they prepared to do so? One hundred and thirty-two modified Revised Wylie Inventories were mailed to college/university athletic trainers to examine their educational preparation and experiences with counseling in various areas. Most athletic trainers surveyed reported that they were predominantly counseling in the areas of injury prevention, injury rehabilitation, and nutrition, and felt academically prepared to do so. However, it was reported that preparation to counsel in other less common areas (eg, family matters, financial matters, etc) was not adequately addressed in academic programs. The athletic trainers surveyed sought continuing education in order to meet the other counseling needs of student-athletes. Although they used several psychological referral services, it was apparent that most athletic trainers frequently served as counselors on many nonorthopedic topics. We suggest that athletic training educators consider incorporating both academic knowledge and clinical experience in a wider variety of counseling areas into their curricula.
Keywords: dept.hms; ⛔ No DOI found